2012
DOI: 10.1159/000336803
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Cell-Mediated Immune Biomarkers in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome and Depression: Inflammatory Markers Are Higher in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome than in Depression

Abstract: Background: Depression is an inflammatory disorder while many authors declare myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) to be a functional disorder. The aim of the present study is to compare inflammatory and cell-mediated immune (CMI) responses between depression and ME/CFS. Methods: We measured two proinflammatory cytokines (PICs) in plasma, interleukin-1 (IL-1) and tumor necrosis factor-α (TNF-α), with enzyme-linked immunosorbent assays, and serum neopterin with a radioimmunoassay in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 87 publications
3
80
0
Order By: Relevance
“…Neopterin -levels of plasma neopterin are increased in depressed patients (Celik et al, 2010, Maes et al, 2013, Maes et al, 1994, Maes et al, 2012b, Rybka et al, 2013 and particularly in patients suffering from melancholic symptoms (Maes et al, 2012a, Maes et al, 1994. Greater concentrations of neopterin were also reported in patients suffering from two or more episodes of depression compared to first-episode populations (Celik et al, 2010).…”
Section: Accepted M Manuscriptmentioning
confidence: 98%
“…Neopterin -levels of plasma neopterin are increased in depressed patients (Celik et al, 2010, Maes et al, 2013, Maes et al, 1994, Maes et al, 2012b, Rybka et al, 2013 and particularly in patients suffering from melancholic symptoms (Maes et al, 2012a, Maes et al, 1994. Greater concentrations of neopterin were also reported in patients suffering from two or more episodes of depression compared to first-episode populations (Celik et al, 2010).…”
Section: Accepted M Manuscriptmentioning
confidence: 98%
“…As values fluctuated significantly only in the MD group, an influence of this disease on the immune system also seems possible. Several studies have found characteristic alterations in the immune status of depressed persons [10, 11, 32, 47], suggesting a proinflammatory immune status in these patients. The female MD subgroup showed highly significant fluctuations in activated T lymphocytes (CD3 + CD25 + ), which is also an indicator of inflammation, once more suggesting an altered and possibly more fragile cellular immune status in depressed patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several have tried to explain the etiology of SFD, such as childhood experiences of illness [5], high interoceptive awareness [6, 7], or misinterpretation of complaints as illness [7]. There are indications that the immune system may be causally involved, but study results vary [8-10]. Taking all these findings together, it is further strengthened that depression and SFD are two frequently overlapping clinical conditions having both been related to immunological changes [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations